Observaciones sobre el gusano cachon de la yuca Erynnyis ello (L) y algunas recomendaciones para su manejo (CIAT Septiembre, 1978 para el dia de campo en caicedonia) - Reyes, J.A.; Arias, B.; Martin, C (International Center for Tropical Agriculture, 1978)
For the biological control of Ernnyis ello, an application of Bacillus thuringiensis (400-500 g/ha for aerial applications or 2-3 g/l of water for land applications), together with a surfactant with adherent properties, is recommended. When a hornworm population increase is foreseen due to the increase in the no. of eggs laid, another good control measure is the release of the egg parasite Trichogramma spp. in the cassava fields; T. australicum has been found to be the most effective. Other effective practices for reducing the hornworm populations are the establishment of colonies of Polistes, a predator of the larvae, in bamboo shelters 1.8-2.0 m high, covered with palm leaves, and the collection of the Erinnyis pupae found in the debris around the plants. The biological cycle of the hornworm and the sexual differentiation of the pupal stage are explained and illustrated. (CIAT)